Social isolation among indigenous college students in Peru: the role of language, culture, and acculturation - Guerra Ayala, Margit Julia; Valdivia Laura, Carlos Antonio; Bernedo Perez, Hania Nancy; Florez Lucana, Apolinar; Tapia Condori, Rildo Raul; Durand-Gómez, Emma Lourdes (Frontiers in Sociology, 2025)
Social isolation is a significant challenge faced by university students from indigenous Quechua and Aymara communities in Peru, often stemming from language barriers, cultural differences, and the pressure to assimilate into a predominantly Spanish-speaking academic environment. Isolation can negatively affect emotional wellbeing and academic success. This research aims to determine how psychological acculturation and Spanish L2 (second language) proficiency influence social isolation. The study included 202 university students from Quechua and Aymara communities in Peru (aged 18–30; 69.8% female, 30.2% male; 33.7% Quechua, 66.3% Aymara). A newly developed Psychological Acculturation Scale assessed cognitive and emotional adaptation processes, showing good reliability (ω = 0.774) and an adequate model fit in Confirmatory Factor Analysis, with CFI = 0.923, TLI = 0.899, SRMR = 0.0521, and RMSEA = 0.066. The Isolation and Loneliness Questionnaire (CAS), adapted for university students, was used to assess social isolation. Spanish L2 proficiency was evaluated using the CEFR (Common European Framework of Reference for Languages) descriptors. A non-experimental, quantitative design was employed, using simple linear regression to analyze the predictive power of psychological acculturation and Spanish L2 proficiency on social isolation. ANCOVA tested the moderating effects of gender, culture of origin, and academic performance. Results indicated that Spanish L2 proficiency strongly predicted social isolation, explaining 82.3% of the variance independently and 85.6% when combined with psychological acculturation. Interaction effects between gender, cultural background, and academic performance were not significant. This study provides evidence for the crucial role of language proficiency in the social integration and academic success of indigenous students, calling for targeted interventions that address linguistic barriers and promote cultural understanding.